CHANGES IN THE SCOPE OF PROTECTION OF NEMO TENETUR SE DETEGERE PRINCIPLE DUE TO THE MODIFICATIONS INTRODUCED BY LAW 12.654/12 IN CRIMINAL INVESTIGATIONS: THE (IN) CONSTITUTIONALITY OF COERCIVE COLLECTION OF GENETIC MATERIAL TO DETERMINE THE GENETIC PROFILE - Vaz Silva, Rodrigo (Unoesc International Legal Seminar, 2017)
This article deals with the impact of Law 12.654, passed in 2012, in the scope of protection of the principle “nemo tenetur se detegere”. The introduction of compulsory identification of the genetic profile of the person criminally investigated as a means of evidence, with the inclusion of such measures among those listed as a way of criminal identification (Law 12.037), fills the legislative vacuum of matter, becaming imperative the analysis of compatibility of Law 12.654 with the Federal Constitution and the Human Rights Treaties which Brazil is a signatory